What's Going On in a Graphic Novel?. (1st March 2018) - Smith, Jennifer M.; Pole, Kathryn
Abstract: The increase of graphic novels in libraries and schools and on award lists illustrates one way that children's literature is changing. This article explores the relation between words and illustrations in a popular graphic novel. The multimodal format of graphic novels requires readers to consider the words, graphics, panel sizes, and uses of color and line. Thus, the authors propose that (a) students need explicit instruction on how to read graphic novels, (b) graphic novel reading requires slow reading to attend to the details, and (c) opportunities to talk about text are necessary to explore the complexities of graphic novels.